Compositermes bani sp.n. (Isoptera, Termitidae, Apicotermitinae), a new species of soldierless termite from Bolivia - Carrijo, Tiago F.; Scheffrahn, Rudolf H.; Křeček, Jan (Zootaxa, 2015)
Species of neotropical Apicotermitinae (Termitidae) are soldierless, restricting species identification in this group to workers or seasonally present winged imagos. All neotropical Apicotermitinae were placed in the genus Anoplotermes, until Mathews (1977) described two new genera, Grigiotermes and Ruptitermes. Fontes (1986) described two more genera, Aparatermes and Tetimatermes. Twenty years passed without any taxonomic advances in this group until Scheffrahn et al. 2006 described two new Anoplotermes species from the West Indies and Bourguignon et al. 2010 described Longustitermes manni, (=Anoplotermes manni Snyder), Anoplotermes janus, and placed six other species into synonymy. Finally, Scheffrahn 2013 described a new genus and species, Compositermes vindai, characterized by a ring of sclerotized paddles at the junction of the enteric valve seating (EVS) and paunch (P3).